Automated Smart Healthcare Monitoring System - K., Senthil Kumara Raja; S., Vignesh Raja; V., Arockia Joshwa; R., Yokesh (Journal of Ubiquitous Computing and Communication Technologies, 2025)
This research presents the design and implementation of a fully automated chair equipped with sensors to assess the health status of patients. The chair measures vital signs such as weight, blood pressure, heart rate, oxygen level, and temperature. The system is fully integrated with the ThingSpeak IoT cloud platform. The collected data in ThingSpeak is processed by a machine learning model in the cloud to detect sudden changes in vital signs and send alerts to notify doctors. The proposed method utilizes K-means clustering to identify abnormal or sudden variations in vital signs. Future developments aim to integrate the chair with a user-friendly application that includes patient details, a video call appointment option, medication and appointment reminders, and outpatient ID (OP ID) generation.
Keywords: Health Monitoring; Machine learning; ThingSpeak; IoT (Internet of Things); Cloud Platform